Brown Planthoppers population in local rice varieties based on cellulose, hemicellulose and lignin content. (March 2019) - Wijayanti, R; Sholahuddin,; Supriyadi,; Poromarto, S H
Abstract: Brown planthoppers (BPH), Nilaparvatalugens, is insect pest in rice cultivation attack rice in all stages resulting growth retardation or stunting. In serious attack whole rice field can be lost. Some variety are resistant due to different plant cell walls. As known, cell wall components are cellulose, hemicellulose and lignin. For that, this research was aimed to evaluate BPH population in local rice varieties which have different content of cellulose, hemicellulose, and lignin. In this study, cellulose, hemicellulose and lignin content was analyzed using Cesson methods. The rice variety observed were aromatic (Rojolele, Pandanwangi, Mentikwangi, Mentiksusu), non-aromatic (Saudah/Klaten red rice, Slegreng/Wonogiri red rice, Rojopusur, Srikiti, Black rice/padi hitam Wonogiri), and Inpari 13 as control. The results showed that there were differences in cellulose, hemicellulose, and lignin content among the rice varieties. Cellulose content in local rice stems ranged from 24-27%, hemicellulose 22-31%, and lignin 10-14%. The highest cellulose content was in Inpari 13 and the lowest was in Rojopusur. Slegreng has highest hemicellulose, > 30%, and Pandanwangi has the highest lignin. According to the results, it is concluded that the different incell wall component (cellulose, hemicellulose and lignin) of local rice did not affect to the BHP population.